2002
DOI: 10.1093/jnci/94.8.597
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Urokinase-Type Plasminogen Activator Receptor on Human Glioblastoma Tumors With Diphtheria Toxin Fusion Protein DTAT

Abstract: DTAT may have potential for intracranial glioblastoma therapy because of its ability to target tumor cells and tumor vasculature simultaneously and its apparent lack of systemic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
66
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 36 publications
1
66
0
Order By: Relevance
“…Several potential anti-cancer agents have been developed by fusing ATF with other molecules, such as ATF-PAI2CD, 36 ATF-albumin, 37 ATF-domain 2 of bikunin, 38 and ATF-DTx. 39 Each of these hybrid molecules has been tested in animal experiments and all of them exhibit potential anti-cancer activities. In 1993, Crowley et al, constructed an antibody-like molecule consisting of the cell binding domain of u-PA (1-137 aa) linked to the Fc fragment of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Several potential anti-cancer agents have been developed by fusing ATF with other molecules, such as ATF-PAI2CD, 36 ATF-albumin, 37 ATF-domain 2 of bikunin, 38 and ATF-DTx. 39 Each of these hybrid molecules has been tested in animal experiments and all of them exhibit potential anti-cancer activities. In 1993, Crowley et al, constructed an antibody-like molecule consisting of the cell binding domain of u-PA (1-137 aa) linked to the Fc fragment of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 has been shown to bind IL-4R. 28,36 Our studies showed that toxicity was reduced in the knockouts that did not have IL-4 receptor. These studies indicated that the hepatotoxicity was attributed to specific binding of the IT, and not to the nonspecific presence of DT.…”
Section: Discussionmentioning
confidence: 64%
“…36 U373 MG or Neuro 2a cells at 1 3 10 4 /well or Daudi cells at 1 3 10 5 /well were plated in a 96-well flat-bottomed tissue culture plate. Adherent cells were incubated at 37°C prior to the addition of ITs.…”
Section: Proliferation Inhibition Activitymentioning
confidence: 99%
“…In vitro, DTAT has shown a potent antitumor activity against uPAR-expressing glioblastoma cells (U118MG, U373MG, and U87MG) and human umbilical vein endothelial cells. In vivo, DTAT caused a significant regression of small U118MG cell-induced tumors in mice (Vallera et al, 2002). Tf-CRM107 is a conjugate of human transferrin (Tf) and a genetic mutant of diphtheria toxin (CRM107) that lacks native toxin binding.…”
Section: Diphtheria Toxinmentioning
confidence: 99%